The CRP/PAB ratio outperforms the LRINEC score in early diagnosis of Fournier's gangrene - Jin-Liang Zhu; Hong-Jian Gao; Zhi-Tao Yin (Surgery in Practice and Science)
Background: Fournier's gangrene (FG) is scarce and potentially fatal disease. Although the Laboratory Risk Indicator for Necrotizing Fasciitis (LRINEC) score was established in 2004, its reliability as a diagnostic tool to differentiate between FG and perianal abscess is still debated. The objective of this study was to assess the reliability of the LRINEC score and other relevant inflammatory markers. The diagnostic effectiveness of these inflammatory factors was evaluated and compared. Methods: Retrospective observational study of patients with FG or with perianal abscess. Fifty-two patients with FG and 39 patients with perianal abscess treated in Shenyang Coloproctology Hospital between January 2019 and December 2023 were enrolled in the study. Results: The area under the ROC curve (C-statistic) of a LRINEC score ≥6 for diagnosing FG was 0.736. Inflammatory markers, including C-reactive protein (CRP), procalcitonin (PCT), prealbumin (PAB), neutrophil-to-lymphocyte ratio (NLR), and systemic immune inflammation index (SII), demonstrated better diagnostic ability compared to the LRINEC score. Particularly, the compound inflammatory factor of CRP-to-PAB (CRP/PAB) ratio exhibited superior diagnostic ability compared to other markers (C-statistic: 0.908; p < 0.001). Conclusions: The LRINEC score demonstrated only modest discriminative performance in this study. Patients with PAB< 91mg/L and a CRP/PAB≥ 1.52 should undergo careful evaluation for the presence of FG. The elevated CRP/PAB ratio is considered an early indicator for FG, particularly in distinguishing it from deep perianal abscesses. Further investigation is warranted in future studies to support these findings.